Proceso de atención de enfermería en adulto mayor con coledocolitiasis. - Muñoz Velásquez, Génesis Ariana (2021)
Choledocholithiasis is the presence of stones or stones in the bile duct and is one of the diseases that can occur in up to 20% of cases of cholelithiasis, currently the correction treatment is purely surgical laparoscopic cholecystectomy¨ but this technique is debated when approaching patients surgically. The objective of this clinical case was to apply the nursing care process to a patient with a medical diagnosis of choledocholithiasis, hospitalized in the surgery area of the General Hospital Gustavo Domínguez. Because it is a very important issue, the nursing professional must implement biosafety, asepsis and antisepsis measures and prior hand washing at the time of carrying out the activities that were taught based on the nursing diagnosis and the nursing care process, to provide direct care to the patient, in order to reduce the percentage of pathogenic microorganisms when cleaning the wound in a sterile way. Through this case it was possible to conclude that the nursing care process, medical treatment and nursing interventions are essential for the recovery of the patient, providing quality care and warmth to patients with choledocholithiasis.